UMPJJ- WCS (Wages Claims System) through web / Ong Min Tat - Ong , Min Tat (2001)
The final year thesis paper has divided into 2 major parts which are the WXET 3181 Latihan Ilmiah I and WXET 3182 Latihan Ilmiah II. The division of these 2 thesis paper is based on the 7 major stages in SDLC (System Development Life Cycle) context which WXET 3181 Latiban Ilmiah I covers 3 major stages in SDLC whereas WXET 3182 Latihan Ilmiah II covers the remaining 4 major stages in SDLC. The WXET 3181 Latihan Ilmiah I is a special 4 credit hours thesis paper which does not involve any lecture or tutorial classes but to let the FSKTM final year students to involve themselves in their individual exclusive project of system development which has approved by the Dean Faculty of Computer Science and Information Technology of University of Malaya, Kuala Lumpur. After completion of the WXET 3181 Latihan Ilrniah I, each of the students is required to prepare a thesis report and presentation on what have been done by them in the early stages of their system development from their research. My thesis working paper is mainly focus on the web based application system development of wages claim system for PJJ(Distance Learning Center) University of Malaya. I call this system as UMPJJ-WCS. UMPJJ-WCS enables UM PJJ (Distance Leaming Center) in managing the wages claims for every lecturers in every semester effectively and efficiently. It is a web-based application system developed with the objectives of implementing the idea of information systems on the WWW. As a web-based application, the client terminals work in tandem with the server, operating over the internet during a request or response session. The server terminal contains all the related documents, data storage, and business rules. There are 2 sections in a client terminal - the authorized users and administrator. The administrator has the full access to all databases and documents whereas the users access is somehow limited. Besides, the administrator is to do administrative task such as maintaining system contents, users list, and users personal particulars. A user will be able to browse through the web and making request for their wages claims through UMPJJ-WCS.